HIDRORENGKAH KATALITIK MINYAK KULIT BIJI JAMBU METE (CNSL) MENJADI FRAKSI BENSIN DAN DIESEL - Lisna Efiyanti; Wega Trisunaryanti (BRIN Publishing, 2014)
This research aimed to look into the hydocracking potential of CNSL into fuel fraction with the aid of catalyst. Thebased materials of catalyst as used were Y-zeolite from Japan and Nickel metal (E-Merck). NiO/ZY catalyst wasprepared with wet impregnation method using salt precursor Ni(NO ) .6H O into Y-zeolite as a supporting stuff.Catalyst characterization was determined by gravimetry method to examined acidity of catalyst with pyridine base as aadsorbate base and catalyst porosity using Surface Area Analyzer (NOVA-1000). Hydrocracking process was carriedout in a fixed-bed system reactor using NiO/ZY catalyst at temperature of 400°C with H flow rate of 20mL/min, andthe ratio of feed/catalyst equal to 4. The results product was analyzed using Gas Chromatography (GC). Results showedthat CNSL hydrocracking with NiO/ZY catalyst brought out liquid product as much as 80.03% in portion withselectivity on gasoline, diesel and heavy oil are 38,47%, 25,88% and 15, 74%, respectively.